PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOR DAN TURNOVER INTENTION PADA PEGAWAI PT. BANK BNI LIFE INSURANCE CABANG KOTA PEKANBARU - Ananda, Wahyu; Fitri, Kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research was conducted at PT. Bank BNI Life Insurance Branch of Pekanbaru. With the aim to identify and analyze the effects of job satisfaction and organizational commitment to the organization citizenship behavior and employee turnover intention in PT. Bank BNI Life Insurance Branch of Pekanbaru. The population in this study were all employees at PT. BNI Life Insurance Pekanbaru. The sample used in this study were a total of 109 employees and data processing using path analysis with SPSS.Pursuant to result of solution and research which have been conducted at previous chapter, hence at this shares can be taken by some conclusion, that is: zenship behavioratPT. Bank BNI Life Insurance Branch of Pekanbaru, satisfactions of work have an effect on positive and signifikan to turnover intentionemployees atPT. Bank BNI Life Insurance Branch of Pekanbaru,organization commitment have an effect on positive and signifikan to turnover intentionemployees atPT. Bank BNI Life Insurance Branch of Pekanbaru,organization citizenship behavior have an effect on positive and signifikan to turnover intentionemployees atPT. Bank BNI Life Insurance Branch of Pekanbaru,satisfactions of work have an effect on positive and signifikan to turnover intentionemployees to pass the organization citizenship behavior atPT. Bank BNI Life Insurance Branch of Pekanbaru, and organization commitment have an effect on positive and signifikan to turnover intentionemployees to pass the organization citizenship behavior atPT. Bank BNI Life Insurance Branch of Pekanbaru.Keyword: Satisfactions, Commitment, Organization Citizenship Behavior, and Turnover Intention.